Wacana Tayangan Trans 7 tentang Pondok Pesantren Lirboyo: Analisis Sentimen pada Media Sosial Instagram akun@santrikeren - Lestari, Viola Ananda Ayu (Journal of Islamic Communication Studies, 2026)
The development of digital media has fundamentally transformed patterns of public communication, including the discourse of Islam in Indonesia. One phenomenon that has sparked widespread public debate is a broadcast by Trans7 depicting the lives of students (santri) at Pondok Pesantren Lirboyo, which generated both support and criticism across social media platforms. This study aims to analyze public sentiment and emotional responses to the broadcast through comments posted on the Instagram account @santrikeren, and to examine how digital discourse is constructed as a form of social representation of the pesantren community. The research employs a descriptive qualitative method with a content analysis approach supported by Orange Data Mining software. Data were collected through the scraping of Instagram comments, followed by preprocessing, sentiment classification, and emotion analysis. The findings reveal that public sentiment is predominantly neutral (55%), followed by negative (34%) and positive (10%) responses. The distribution of emotions indicates the dominance of joy and surprise, reflecting both pride and moral astonishment regarding the representation of pesantren in mainstream media. Discourse analysis further demonstrates that the pesantren public utilizes social media as a space of articulation to produce counter-discourse in response to media framing. These findings affirm that social media functions not only as a space for emotional expression but also as an arena of digital da‘wah that reinforces Islamic identity, ethical conduct (adab), and morality within the modern public sphere.